4-Phenylbutyric acid and metformin decrease sensitivity to pentylenetetrazol-induced seizures in a malin knockout model of Lafora disease. Issue 5 (22nd March 2017) - Sánchez-Elexpuru, Gentzane; Serratosa, José M.; Sanz, Pascual; Sánchez, Marina P.
Abstract : Lafora disease (LD) is a rare adolescent-onset progressive myoclonic epilepsy caused by loss-of-function mutations either in the EPM2A gene encoding laforin or in the EPM2B gene encoding malin. Mouse models with deletion in the Epm2a or the Epm2b gene show intracellular aggregates of polyglucosans (Lafora bodies) and neurological complications that resemble those observed in patients with LD. In the absence of laforin or malin expression, mice also show different degrees of hyperexcitability, as reflected by an enhanced response to the convulsant drug pentylenetetrazol (PTZ). Malin knockout mice treated with 4-phenylbutyric acid (4-PBA) and metformin showed decreased amounts of Lafora bodies and polyubiquitin protein aggregates in the brain, diminished neurodegeneration, and amelioration of some neurological conditions. In this study, we analyzed the action of 4-PBA and metformin treatments on response to PTZ in a malin knockout model of LD. Both treatments decreased seizure susceptibility, bringing about a reduction in both seizure number and length, and eliminated the mortality induced by PTZ. These results show a neuroprotective role of 4-PBA and metformin and extend the beneficial effects reported in the malin knockout model of LD Video abstract:http://links.lww.com/WNR/A411 . Abstract : Supplemental Digital Content is available in the text.